(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the legal nature and functions of criminal-law incentive norms under the legislation of the Republic of Uzbekistan. It analyzes the application of legal norms whose official purpose is to ensure the normal functioning of the system of social relations, protect them, and prevent encroachments on them. Incentive norms occupy a special place, classifying them as an independent type of legal norm, existing alongside prohibitive, mandatory, and empowering ones. The article examines incentive norms as a relatively independent means of legal regulation, which is associated with the creation and implementation of a special type of legal norm—incentive norms—and certain legal consequences conditioned and characterized by the specific nature of this norm, a possible form of criminal-law coercion provided for criminal behavior.